2012
DOI: 10.1186/1754-6834-5-75
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of Zymomonas mobilis under ethanol stress

Abstract: BackgroundHigh tolerance to ethanol is a desirable characteristics for ethanologenic strains used in industrial ethanol fermentation. A deeper understanding of the molecular mechanisms underlying ethanologenic strains tolerance of ethanol stress may guide the design of rational strategies to increase process performance in industrial alcoholic production. Many extensive studies have been performed in Saccharomyces cerevisiae and Escherichia coli. However, the physiological basis and genetic mechanisms involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 42 publications
10
68
2
Order By: Relevance
“…1), which is consistent with a recent transcriptomic study for Z. mobilis under 5% ethanol stress published during the reviewing process of our manuscript [25]. In addition, both studies indicated that ethanol has effects on multiple aspects of cellular metabolism [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…1), which is consistent with a recent transcriptomic study for Z. mobilis under 5% ethanol stress published during the reviewing process of our manuscript [25]. In addition, both studies indicated that ethanol has effects on multiple aspects of cellular metabolism [25].…”
Section: Discussionsupporting
confidence: 90%
“…Gene deletions are possible in Z. mobilis [22]. DNA microarray studies have provided insights into Z. mobilis growth under aerobic and anaerobic conditions [23], under sodium chloride and sodium acetate stress conditions [22], as well as under ethanol and furfural stress [24], [25] that led to insights into its physiology, inhibitor tolerance, and electron transport [26]. Other studies have improved Z. mobilis tolerance to different inhibitors using overexpression of the native hfq gene [27] or Deinococcus radiodurans irrE gene [28].…”
Section: Introductionmentioning
confidence: 99%
“…In E. coli, expression of the CRISPR array is revealed to be highly regulated [38]. In addition, the cas genes seem to express constitutionally which is inferred from the previous transcriptomic analysis in Z. mobilis ZM4 [33]- [35]. Taken together, the CRISPR-Cas system in ZM4 can be expressed under the normal growing condition.…”
Section: Discussionmentioning
confidence: 67%
“…Further, the transcripts of six cas genes in Z. mobilis ZM4 growing at various conditions could be easily detected in the previous transcriptional analysis [33] [34]. For example, the relative transcriptional levels of the cas genes are presented in Table 1, which is retrieved from the transcriptome data in the previous studies [35].…”
Section: Expression Of the Crispr-cas System In Z Mobilis Zm4mentioning
confidence: 96%
“…To further characterize the uncovered sRNAs, we confirmed their expression levels under ethanol levels (5%) that have been reported to stress cell growth and decrease ethanol productivity (53). Three sRNAs (Zms2, Zms6, and Zms18) were expressed differentially under ethanol stress, suggesting that they could be related to regulatory mechanisms of ethanol production or tolerance in Z. mobilis.…”
Section: Discussionmentioning
confidence: 83%